'A most active, enterprising officer': Captain John Perkins, the Royal Navy and the boundaries of slavery and liberty in the Caribbean. (2nd January 2018) - Hamilton, Douglas
ABSTRACT: John Perkins was the most senior black officer in the Royal Navy during the American War of Independence and the French Revolutionary and Napoleonic Wars. He rose through the ranks from a carpenter's enslaved servant in 1759 to post-captain in 1800, and went on to be one of the very first British officials to land in newly independent Haiti in 1804. His career as a spy, gun-runner, naval officer and land owner was one of almost implausible adventure and speaks to the capacity of the maritime service to subvert race and slavery in the Caribbean. His very uniqueness, however, highlights the profound challenges for slaves and ex-slaves in trying to remake themselves as free people.